Walid Nak Dewi Boleh? : Efforts to Prevent Child Grooming Through Virtual Reality (VR)-Based Digital Literacy - Raisya Aulia; Aliyah Putri Chania; Nayla Dinda Saniyya; Achmad Sauri; Azwaldi Azwaldi (Interdisciplinary Social Studies, 2026)
The rapid development of digital technology has increased children's exposure to online environments, creating both opportunities and risks, including the rising phenomenon of child grooming. This study aims to develop and evaluate Virtual Reality (VR)-based digital literacy media as an innovative preventive strategy to enhance students' awareness and understanding of online grooming threats. The research adopts a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through questionnaires, observations, interviews, and documentation involving students, teachers, and experts. The findings indicate that VR-based learning media provides an immersive and interactive experience that significantly improves students' engagement and comprehension of digital safety concepts. Expert validation results show that the developed media is categorised as feasible and highly appropriate for educational use, with strong ratings in material accuracy, media design, and language clarity. The discussion reveals that VR simulations effectively support experiential learning by allowing students to recognise grooming patterns and practise decision-making in safe, simulated digital environments. In conclusion, VR-based digital literacy is an effective and innovative learning medium for preventing child grooming, as it increases awareness, understanding, and behavioural readiness among students, while also offering strong potential for integration into future digital education strategies.